Functional analysis of dendritic cell-T cell interaction in sarcoidosis. - Kulakova, N; Urban, B; Mcmichael, A; Ho, L (2010)
The primary cause of the intense immune response in sarcoidosis is unclear. Potentially, a functional abnormality in dendritic cells (DCs) could cause a reduction in clearance of antigen and downstream persistence in immune activity. In this study, we investigate the interaction between monocyte-derived dendritic cells and T cells in patients with sarcoidosis compared to normal controls (n = 8 each) by examining the kinetics of autologous and allogeneic mixed leucocyte reactions over 9-10 days. We found markedly depressed proliferation kinetics in autologous DC-peripheral blood mononuclear cell (PBMC) co-cultures from sarcoid patients compared to normal subjects. In allogeneic experiments PBMCs from patients showed a reduced response to allogeneic DCs from a single donor, but no difference was observed in the ability of patients and control DCs to stimulate proliferation of allogeneic PBMC from a single donor. We conclude that there is a markedly impaired autologous mixed leucocyte reaction (MLR) in sarcoidosis patients. In allogeneic MLR, monocyte-derived DCs in sarcoidosis were able to stimulate T cells normally, but PBMCs responses were reduced. This contradicts recent published studies on ex vivo isolated myeloid DCs from sarcoidosis patients although, potentially, an in vivo conditioning factor, which reduces DC function in sarcoidosis, could be a unifying explanation for the contrasting findings.